Identifikasi Kearifan Lokal Masyarakat Hutan Larangan Adat Rumbio, Kabupaten Kampar Terhadap Perlindungan Hutan - Anas Ritonga; M. Mardhiansyah '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The aim of the research are 1) to identify local wisdom Rumbio forest communities to the forest protection and forest management, 2) to determine Rumbio communitites strategies on the management of sustainable forest at protected ban forest. This research was conducted at Rumbio village, Kampar regency, Riau Province. The local communities of forest Rumbio subject is to certain characteristics. Major characteristics subject is local communities Rumbio, Kampar. This research was carried out using method survey. Data were taken by using Snowball sampling technique which is nine informant as samples. Data were analyzed using Descriptive Analysis. Result showed that 1) a. local wisdom has been applied in the communities at ban forest and there are some regulation that should follow by communities such as like not to cut trees at ban forest or held and activity that may harm the forest it self, b. local wisdom for asking communities to plant the trees and build houses at appropriate places, 2) Forest protection strategies in ban Rumbio forest are: a) build security posts, established of the Rural Forestry Extension Centers (RFEC), greening, monitoring and sanctions for people who break the rules, b) kind of effort to keep ban forest and sustain the forest is choosing at the forest and communities garden, c) form of socialization customs regulations Rumbio is notification to young children as the next generation of indigenous communities through involvement in the traditional procession, announcements in indigenous associations.   Key Words: local wisdom, local communities Rumbio, forest protection